Corrosion decomposition and mechanical behaviors of As‐cast Mg–xZn–Zr alloys. Issue 9 (16th March 2020) - Li, Xuewu; Zhou, Longlong; Shi, Tian; Li, Ben; Yu, Weining; Zhang, Chuanwei; Yan, Pan; Zhang, Qiaoxin; Tian, Haoliang; Lv, Yuan
Abstract: Developing new‐type alloy materials with excellent decomposition properties and mechanical behaviors is a thorny issue for preparing fracturing balls in oil exploitation. As‐cast Mg– x Zn–Zr alloys designed by regulating Zn contents have been fabricated in this study. Compressive strength and immersion corrosion test have been investigated to assess their feasibility as decomposition materials. Scanning electron microscopy and X‐ray diffract meter have also been used to characterize surface morphologies and phase structures for determining their decomposition mechanism. Results show that matrix phases and secondary phases with discontinuous reticular features form on the alloys. They also achieve excellent mechanical properties to ensure stability and pressure‐maintaining capacity in the decomposition process in chloride environment. Meanwhile, with Zn content and immersion time increasing, galvanic corrosion effect strengthens leading to accelerated specific mass loss rates of the alloys. Rapid corrosion decomposition of the alloys mainly attributes to anodic dissolution of matrix phases, exfoliation of microparticles, and poor resistance of corrosion products to the decomposition process. This study provides positive insight into the preparation of new‐type Mg alloys for guaranteeing fast decomposition of fracturing balls and also ensuring their compressive strength stability. Abstract : Compressive strengths of as‐cast Mg– x Zn–Zr alloys before and after decomposition are far higher than pressure‐bearing requirement for fracturing balls. Alloys also achieve higher mass loss rates than frequently used decomposable Mg–RE–Zr and Mg–Al–Zn–RE materials. Rapid corrosion of alloys attributes to anodic dissolution of matrix and poor resistance of corrosion products to the dissolution process.